EPIGENETICS IN MELANOMA (International Integralize Scientific, 2026)
Melanoma is the most lethal skin cancer and presents high biological, clinical, and therapeutic heterogeneity. In recent years, scientific evidence has demonstrated that epigenetic mechanisms play critical roles in tumor initiation, progression, metastasis, and the development of therapeutic resistance. This bibliographic study aimed to synthesize the state of the art on epigenetics applied to melanoma, discussing its molecular basis, prognostic implications, and potential therapeutic applications. The analysis of the results showed that epigenetic alterations contribute to tumor plasticity and variability in response to targeted therapies and immunotherapies, in addition to pointing to the potential use of epigenetic biomarkers in the diagnosis and monitoring of the disease. It is concluded that a deeper understanding of the epigenetic mechanisms associated with melanoma constitutes a fundamental axis for the advancement of personalized medicine, opening perspectives for the development of new therapeutic strategies and greater clinical precision in the management of this neoplasm.
Keywords: Melanoma; epigenetics; DNA methylation; biomarkers; immunotherapy.